The application of digital console game for the treatment of children with sensory integration dysfunction: Parental perspective - Lee, I-Ching; Chuang, Tsung-Yen (Medical and Health Science Journal, 2013)
Objective: The present study aims to investigate the effect of applying digital console game to the treatment of children with sensory integration dysfunction and to explore the experience and feedback from parents' perspective. Method: 4 school-aged children with sensory integration dysfunction (SID) and their parents participated the present study. Participants received 12-week training programs which consists of their regular therapeutic treatment once a week and additional training activities (i.e., designed Digital Console Game activities) once a week. Observations and interviews were conducted. Results: Results derived from the direct observations of children's behaviors and the parents’ feedback confirmed that the characteristics of the digital console games may positively reinforce the inner drive of children with SID and further elicit their motivation on treatment participation and engagement. Conclusion: Parents of children with SID support the positive effects of applying digital console games into the regular therapeutic treatment of their children had received. The child's playful experience may increase their motivation to engage in the therapeutic process and distract their focus away from the unpleasant feeling of treatment, and then further encourage their continuation of chronic treatment regimes. It is hoped to provide an innovative approach to SID therapy.
Keywords: Parents; počítače; dítě; rodiče; Video Games; Child; Computers; výzkumný projekt; somatosenzorické poruchy; Somatosensory Disorders; Humans; Research Design; lidé; videohry